Relationship of Balance And Leg Muscle Strength To Lower Passing Ability in Young Soccer Athletes - Arief Dwi Arnanto; Purwono Sidik Permono (Journal of Physical Education and Sports, 2026)
This study aims to analyse the relationship between dynamic balance and leg muscle strength and their impact on the accuracy of underhand passes in youth soccer players. The method used is a quantitative correlational design, with a sample of 21 SSB Garuda Lenggerong U-17 players selected randomly. Data were collected through the Y Balance Test (balance), Standing Broad Jump (lower limb muscle strength), and short pass test (accuracy of underhand passing), then analysed using the Shapiro-Wilk normality test, Pearson correlation, and linear regression. The results showed that lower limb muscle strength had a significant correlation with passing accuracy (r = 0.459; p < 0.05), while balance did not (r = 0.333; p > 0.05). Regression analysis revealed that both variables together contributed 35.87% to passing accuracy, with lower limb muscle strength as the dominant predictor (76.8% relative). These findings suggest that physical training for youth soccer players should emphasise the development of lower limb strength to improve passing accuracy. However, balance training remains relevant in the context of holistic soccer skills.